2020
DOI: 10.5194/os-16-831-2020
|View full text |Cite
|
Sign up to set email alerts
|

An approach to the verification of high-resolution ocean models using spatial methods

Abstract: Abstract. The Met Office currently runs two operational ocean forecasting configurations for the North West European Shelf: an eddy-permitting model with a resolution of 7 km (AMM7) and an eddy-resolving model at 1.5 km (AMM15). Whilst qualitative assessments have demonstrated the benefits brought by the increased resolution of AMM15, particularly in the ability to resolve finer-scale features, it has been difficult to show this quantitatively, especially in forecast mode. Applications of typical assessment me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…This effect contributes to some lower RMS difference computed with Aquarius than with CCI L4 SSS. We identified it by looking at r 2 , but methodologies such as the ones developed in the high resolution modeling community (Crocker et al, 2020) could be investigated to better quantify the accuracy of high-resolution fields relative to lower resolution fields. Wavenumber spectral analysis, such as the one performed on sea surface height by (Dufau et al, 2016), should also be studied in order to validate dynamical features of SSS at various spatio-temporal scales.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…This effect contributes to some lower RMS difference computed with Aquarius than with CCI L4 SSS. We identified it by looking at r 2 , but methodologies such as the ones developed in the high resolution modeling community (Crocker et al, 2020) could be investigated to better quantify the accuracy of high-resolution fields relative to lower resolution fields. Wavenumber spectral analysis, such as the one performed on sea surface height by (Dufau et al, 2016), should also be studied in order to validate dynamical features of SSS at various spatio-temporal scales.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…This is related to a lag between the model and observations and a potential double penalty effect in the verification as a result as well as possible cancellation errors in GS12L4EUK-AN. Previous studies demonstrated that metrics based on direct point matchup between model data and observations might often lead to the double penalty effect (Crocker et al, 2020),…”
Section: Comparison Of Configuration Performancementioning
confidence: 99%
“…Although relative changes in T02 metrics and wave Dir show an overall significant improvement (>25% in RMSD and 10% in bias) of these diagnostics when currents and higher resolution are introduced, a larger spread on the observation-model differences for Hs is also observed. This is considered to be linked to the double penalty effect (Crocker et al, 2020), where features are well predicted but misplaced with respect to the observations. Imminent system developments include: (i) the use of sea point wind forcing in the SMC grid, improving the wind transfer between atmosphere and ocean; and (ii) the optimisation of the models in line with model resolution.…”
Section: Summary and Future Developmentsmentioning
confidence: 99%
“…Neighbourhood-based methods in particular have become popular due to the relative ease of computation and intuitive interpretation. Recently, one such neighbourhood spatial method was demonstrated as an effective approach for exploring the benefit of higher resolution ocean forecasts (Crocker et al, 2020). Another class of methods focuses on how well particular features of interest are being forecast.…”
Section: Introductionmentioning
confidence: 99%